Effects of the Application of Dense Phase Carbon Dioxide Treatments on Technological Parameters, Physicochemical and Textural Properties and Microbiological Quality of Lamb Sausages - Szerman, Natalia; Wei, Li Rao; Xin, Li; Yang, Yang; Vaudagna, Sergio Ramon; De Quan, Zhang (2018)
The effects of different dense phase carbon dioxide (DPCD) treatments were evaluated on technological parameters, physicochemical and textural properties and microbiological quality of lamb sausages. Sausages were prepared using lamb meat (Longissimus dorsii, 68.6 % w/w), lamb fat (17.2 % w/w), water (12.9 % w/w) and NaCl (1.37 % w/w). Raw sausages were subjected to different CO2 pressures (10, 20 and 30 MPa) at 60 °C–30 min and treatment times (2, 14 and 25 min) at 55 °C–10 MPa. Weight loss, pH and total expressible fluid increased significantly (p < 0.05) as pressure increased from 0 to 30 MPa. These parameters also increased significantly (p < 0.05) as treatment time increased (at 10 MPa). The increase in CO2 pressure and treatment time significantly (p < 0.05) modified internal and surface color parameters. Lightness and b* values increased, whereas redness (a*) decreased. Also, the increase in CO2 pressure and treatment time significantly (p < 0.05) increased Warner–Bratzler shear force and textural parameters values. DPCD treatments may modify meat proteins, which may lead to weak interactions among proteins and formation of gel-like structures. Regarding microbial inactivation, the highest reductions in microbiological counts (2 Log CFU g−1) were obtained applying a CO2 pressure of 20 MPa at 60 °C for 30 min.